Additive‐Morphology Interplay and Loss Channels in "All‐Small‐Molecule" Bulk‐heterojunction (BHJ) Solar Cells with the Nonfullerene Acceptor IDTTBM. (15th December 2017) - Liang, Ru‐Ze; Babics, Maxime; Seitkhan, Akmaral; Wang, Kai; Geraghty, Paul Bythell; Lopatin, Sergei; Cruciani, Federico; Firdaus, Yuliar; Caporuscio, Marco; Jones, David J.; Beaujuge, Pierre M.
Abstract: Achieving efficient bulk‐heterojunction (BHJ) solar cells from blends of solution‐processable small‐molecule (SM) donors and acceptors is proved particularly challenging due to the complexity in obtaining a favorable donor–acceptor morphology. In this report, the BHJ device performance pattern of a set of analogous, well‐defined SM donors—DR3TBDTT (DR3 ), SMPV1, andBTR —used in conjunction with the SM acceptorIDTTBM is examined. Examinations show that the nonfullerene "All‐SM" BHJ solar cells made withDR3 andIDTTBM can achieve power conversion efficiencies (PCEs) of up to ≈4.5% (avg. 4.0%) when the solution‐processing additive 1, 8‐diiodooctane (DIO, 0.8% v/v) is used in the blend solutions. The figures of merit of optimizedDR3:IDTTBM solar cells contrast with those of "as‐cast" BHJ devices from which only modest PCEs <1% can be achieved. Combining electron energy loss spectrum analyses in scanning transmission electron microscopy mode, carrier transport measurements via "metal‐insulator‐semiconductor carrier extraction" methods, and systematic recombination examinations by light‐dependence and transient photocurrent analyses, it is shown that DIO plays a determining role—establishing a favorable lengthscale for the phase‐separated SM donor–acceptor network and, in turn, improving the balance in hole/electron mobilities and the carrier collection efficiencies overall. Abstract : A set of structurally analogous small‐molecule (SM) donors with distinct side‐chain manifolds shows significant differences in their performance patterns in bulk‐heterojunction (BHJ) devices with the nonfullerene SM acceptorIDTTBM . Reducing the lengthscale of the phase‐separated network between donor and acceptor effectively suppresses nongeminate recombination in the BHJ active layers and improves the carrier mobility balance.